INSTITUTIONAL MODEL OF COCOA PRODUCTION AND AGRICULTURAL DEVELOPMENT - Andi Nuddin; Rustam Abd Rauf; Muh. Fahruddin Nurdin (Universitas Tadulako, 2021)
Since the last 20 years, discussions about Indonesia's position and role in the International cocoa trade have attracted the interest of experts and scientists, not only those in the field of agribusiness and economics, but also able to attract the interest of scientists in the institutional field. This study analyzes how the institutional role in the development of cocoa production through interpretative structural modeling (ISM) analysis approach, with the research location of North Luwu Regency of South Sulawesi. The results of the ISM analysis showed that out of the 13 institutions analyzed, there were nine institutions as priority actors in the development of cocoa production, namely: ((1) Joined Farmer group, (2) Local office for extension services (BP4K), and (3) Extension Officer (4) Private companies, (5) Center for Research/Universities, (6) Local Office for Agriculture and Plantation services, (7) Cocoa Development Center/CDC, (8) Local office for Trade, Cooperatives and Small and Medium Enterprises, and (9) Cocoa Marketing Institute. Furthermore, based on the results of the power-dependent driver matrix mapping, there are three institutions in independent positions, and six other institutions in the linkage position. The six institutions in this linkage position, must be coordinated through effective management, because in addition to affecting the success of the program, feedback can also hinder the development of cocoa production. One of the institutions in the linkage position, namely private companies occupies a key priority position in the development of cocoa production.